An exploratory study of health literacy in the context of health information technology utilization - Ducut, Mary Jastine B.
There has been an observed interest in the phenomenon of self-qualification through the use of health information technology (HIT) in recent years which has been claimed to positively affect personal performance, nutrition, and understanding of one’s mind and body. This is evident in the growth of tracking devices and applications offered in the market. Statistics on mobile phone users, internet users, and online activity in the Philippines seem to suggest the potential for presentation of this trend in the country. However, multiple studies show that the utilization of the technology is complex, requiring new ways of being literate. This study mainly aimed to understand whether health literacy influences the use of HIT tools. It also aimed to uncover the perceptions of Filipino adults on HIT. The relationships among HIT tools used, perceived health literacy and actual health literacy were also examined. Lastly, the study aimed to investigate the influence of health literacy on their perceptions of the technology.